Study of prebored precast pile system - a qualitative approach / Lim Jit Kheng, Ng Wen Kuan and Mohd Farid Ahmad @ Majid - Lim, Jit Kheng; Ng, Wen Kuan; Ahmad @ Majid, Mohd Farid (2006)
In recent years, an alternative foundation system which known as "prebored precast pile system" (PPP) has been introduced in northern region of Malaysia to replace micropile system for areas with shallow rock stratum. It is an integrated system that combining the conventional bored pile and driven pile system. The construction processes involve preboring a slightly bigger hole using micropile machine into rock layer, inserting a precast spun pile section and followed by tapping action to satisfy certain set criteria. Feeling of doubtfulness among the practising engineers about the system has urged the researchers and engineers to look into the problem. A preliminary study has been carried out by conducting face-to-face interview with recognised geotechnical experts in Malaysia, to figure out the acceptance level among them and collect their opinions and comments on the system. The study aims to provide more professional insights and indication on the viability and validity of the system which could be used as a practical reference for practicing engineers. The expert opinions were pooled together and presented in details using subheadings of: System Overview, How to Treat the Gap? Tap-to-Set, Design Considerations, Construction Challenges, Pile Load Test, and Accepted or Not? The result showed that most of the experts cannot accept the system at the present stage until more researches have been done. Preliminary criteria to be fulfilled to apply the system satisfactorily have been identified and future research areas on this system were recommended.